Limit of sensitivity for melting curve screening for α-thalassemia - Sriiam,S. (IOS Press, 2015)
Background: Thalassemia is a major inherited disease in Thailand, with a large number of people being either directly affected or carrying the trait. The Southeast Asian α-thalassemia 1 deletion (--SEA) is the most common α-thalassemia 1 type, with a high number of carriers in Thai population. Individuals who carry the deletion have the potential for having offspring with Hb Bart's hydrops fetalis, the most severe thalassemia syndrome. Given the incidence of this disease, screening for thalassemia is an important tool in diagnosis and many methods have been developed. Objectives: A single tube real-time PCR methodology with a melting curve analysis method has been recently developed, and this work sought to determine the limit of sensitivity of this technique to determine whether it is possible to optimize this methodology and apply it to the single cell level for application in preimplantation genetic diagnosis screening programs. Methods: DNA was extracted from whole blood or isolated peripheral blood mononuclear cells of normal volunteers as well as α-thalassemia 1 (--SEA) carriers. Sensitivity of the melting curve analysis was established with serial dilutions of DNA down to the picogram (pg) level. Results: The melting curve analysis as previously established was sensitive down to 2 ng of DNA. Further optimization increased sensitivity down to 200 pg, but discrimination of a normal allele from an α-thalassemia 1 (--SEA) allele below this level of DNA was not achieved. Conclusion: While advantageous in routine screening programs, real time PCR coupled with a melting curve analysis is not currently suitable for adaptation to pre-implantation diagnosis for alpha thalassemia.